2010
DOI: 10.1098/rsif.2010.0120.focus
|View full text |Cite
|
Sign up to set email alerts
|

Applications of conducting polymers and their issues in biomedical engineering

Abstract: Conducting polymers (CPs) have attracted much interest as suitable matrices of biomolecules and have been used to enhance the stability, speed and sensitivity of various biomedical devices. Moreover, CPs are inexpensive, easy to synthesize and versatile because their properties can be readily modulated by (i) surface functionalization techniques and (ii) the use of a wide range of molecules that can be entrapped or used as dopants. This paper discusses the various surface modifications of the CP that can be em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
269
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(280 citation statements)
references
References 111 publications
5
269
0
6
Order By: Relevance
“…Depending on the type of starting material, the deposition parameters (temperature, pH, U, Q, time) and the choice of solvents and auxiliary components (such as surfactants), the form, texture and order of CPs can be fine-tuned (George et al, 2005;Yang et al, 2005;Abidian et al, 2010). And since Wong et al observed that the shape and growth of (endothelial) cells could be noninvasively controlled by just switching the oxidation state of fibronectin-coated PPy (Wong et al, 1994), and that current flow through PPy would promote protein synthesis and neurite outgrowth (Schmidt et al, 1997), later works exploited this combination of conductivity and particular geometries of CPs for the programmable control of e.g., neurite extension, protein adsorption and cell adhesion, or for the spatially defined release of ions, antibiotics, anti-inflammatories, neurotransmitters and other signaling factors (Abidian et al, 2010;Ravichandran et al, 2010;Sirivisoot et al, 2011;Svennersten et al, 2011). While the roughening of electrodes and the incorporation of biofunctional cues in all cases provide mechanical and biochemical anchoring points for cells, CP coatings are lightweight and usually less brittle than metal deposits.…”
Section: Electrode Functionalization and Post-processing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the type of starting material, the deposition parameters (temperature, pH, U, Q, time) and the choice of solvents and auxiliary components (such as surfactants), the form, texture and order of CPs can be fine-tuned (George et al, 2005;Yang et al, 2005;Abidian et al, 2010). And since Wong et al observed that the shape and growth of (endothelial) cells could be noninvasively controlled by just switching the oxidation state of fibronectin-coated PPy (Wong et al, 1994), and that current flow through PPy would promote protein synthesis and neurite outgrowth (Schmidt et al, 1997), later works exploited this combination of conductivity and particular geometries of CPs for the programmable control of e.g., neurite extension, protein adsorption and cell adhesion, or for the spatially defined release of ions, antibiotics, anti-inflammatories, neurotransmitters and other signaling factors (Abidian et al, 2010;Ravichandran et al, 2010;Sirivisoot et al, 2011;Svennersten et al, 2011). While the roughening of electrodes and the incorporation of biofunctional cues in all cases provide mechanical and biochemical anchoring points for cells, CP coatings are lightweight and usually less brittle than metal deposits.…”
Section: Electrode Functionalization and Post-processing Strategiesmentioning
confidence: 99%
“…While the roughening of electrodes and the incorporation of biofunctional cues in all cases provide mechanical and biochemical anchoring points for cells, CP coatings are lightweight and usually less brittle than metal deposits. Furthermore, unlike metals, both CNTs and CPs are chemically accessible to covalent pre-or post-modification with bioactive molecules (Ravichandran et al, 2010).…”
Section: Electrode Functionalization and Post-processing Strategiesmentioning
confidence: 99%
“…(Andrews et al, 2009) In addition, ion gels enjoy good mechanical strength and electrical conductivity which can be explored for more specialized applications as electrically stimulated controlled release devices (e.g iontophoresis) or artificial muscles as well as for cardiac and/or neuronal tissue engineering applications. (Guiseppi-Elie, 2010;Ravichandran et al, 2010) Finally, the versatility of sol-gel in shaping allows easy adaptations to a wide range of drug delivery applications. (Le Bideau et al, 2011) Functionalization of IL-based polymer gels can be achieved using essentially two different strategies, by the incorporation of the active principle in the solid matrix or exploring the IL as the active principle ingredient, in which a specific biological activity is introduced through one or both of the ions.…”
Section: Drug Delivery and Biomedical Applicationsmentioning
confidence: 99%
“…Various useful properties, like conductivity, reversible oxidation, biocompatibility, hydrophobicity etc of conducting polymers make them desired materials for tissue engineering applications [5] also. The conducting polymers coating not only provide mechanical buffer between the hard device and soft tissues and facilitate charge transport with various cationic and anionic species as done by nerve tissues but also they can be complexed with biologically active counterions and inflammatory drugs and lower the impedance of electrode in the bionic devices.…”
Section: Introductionmentioning
confidence: 99%